2000
DOI: 10.3171/spi.2000.93.2.0222
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective study of an anterior cervical interbody fusion device with a minimum of 2 years of follow-up results

Abstract: Object. Despite variations in technique, inherent problems persist with current approaches to anterior cervical fusion. This study was performed to determine whether anterior cervical fusion performed using an investigational device was safe and effective in the treatment of degenerative cervical disc disorders and whether this device offered advantages over current techniques. Methods. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 18 publications
3
86
0
8
Order By: Relevance
“…The fusion ratio is between 74% and 100%, and exceeds 95% in most series. 3,6,10,13,19,20,[26][27][28] Surgical decompression for cervical spondylosis is beneficial even in elderly patients. Single-level anterior fusion to treat the lesion most responsible for the symptoms is the least invasive choice in the oldest patients.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion ratio is between 74% and 100%, and exceeds 95% in most series. 3,6,10,13,19,20,[26][27][28] Surgical decompression for cervical spondylosis is beneficial even in elderly patients. Single-level anterior fusion to treat the lesion most responsible for the symptoms is the least invasive choice in the oldest patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of different interbody fusion devices, such as cages, surgical strategies have been evolved to achieve anterior cervical fusion. The studies on such promising techniques have been published thereafter 7,12,15,17) . However, Wigfield 18) , in a thorough literature review, concluded that there was limited evidence supporting the use of a cervical interbody fusion device in place of autologous bone.…”
Section: Discussionmentioning
confidence: 99%
“…This study was graded Class II due because no intraobserver reliability was reported for radiographic outcome assessment and allocation concealment was not discussed. 17 In a smaller study with a similar design, Hacker 16 reported on 54 patients who underwent ACDF with either iliac crest autograft or titanium cage placement. Both groups had a 100% fusion rate with good or excellent outcomes similar in both groups.…”
Section: Use Of Titanium Cagesmentioning
confidence: 99%